Calculation of the singlet-triplet magnetic and electro-quadrupole transitions intensity for Ge2 molecule. (3rd June 2022) - Xiao, Lidan; Xue, Jianlei; Liu, Yong; Yan, Bing; Minaev, B. F.
Abstract : Intensity of the parity-forbidden singlet-triplet (S-T) transitions of the Ge2 molecule in the near IR region has been studied by the multi-reference configuration interaction (MRCI) approach with spin-orbit coupling (SOC). Intensity of the b 1 Σ g + − X 3 Σ g, M s = 1 − sub-band is mainly dominated by the spin angular momentum term in the magnetic-dipole transition moment, which arises from the spin current inside the zero-field split sublevels of the ground X 3 Σ g − state. The Einstein coefficients corresponding to vibronic v ′ − v ′ ′ bands 0–(2∼7), 1–(4∼7), 2–(6∼7), 3–7 of the b 1 Σ g + − X 3 Σ g, M s = 1 − transition are in the range of 0.304–0.463 s −1 ; these bands could be detected since they are not overlapped by the allowed rovibronic systems. The magnetic-dipole a 1 Δ g − X 3 Σ g, M s = 1 − is only defined by the orbital angular momentum term and the band intensity is not sufficient for observation. The electric-quadrupole a 1 Δ g − b 1 Σ g + and a 1 Δ g − X 3 Σ g, M s = 0 − transitions have also been calculated to be negligible. The triply forbidden electro-dipole transitions in the IR spectrum of the Ge2 throws new light on this little known domain of diatomic molecular spectroscopy. Highlights The parity-forbidden singlet–triplet transitions of the Ge2 has been studied. Intensity of the  b 1 Σ g + − X 3 Σ g, Ms = 1 − sub-band arises from the spin current inside the zero-field split sublevels of the ground X 3 Σ g − state. Contributions of the a 1 Δg − 1 Πg and X 3 Σ g − − 3 ∏ g  orbital transitions presented in the magnetic-dipole  a 1 Δg - X 3 Σ g, Ms = 1 − transition are negligible. GRAPHICAL ABSTRACT: UF0001